1995
DOI: 10.1056/nejm199507133330203
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Peripheral Neuropathy in Patients with Non-Insulin-Dependent Diabetes Mellitus

Abstract: The prevalence of polyneuropathy among patients with NIDDM increases with time, and the increase may be greater in patients with hypoinsulinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
339
7
15

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(398 citation statements)
references
References 17 publications
23
339
7
15
Order By: Relevance
“…We have shown that neuropathy progressed electrophysiologically at a rate comparable with other studies in patients with type 1 [28] and type 2 diabetes [29]. Alterations in nerve conduction velocity and amplitude have been considered to reflect underlying structural pathology of the myelinated fibres [30].…”
Section: Discussionsupporting
confidence: 80%
“…We have shown that neuropathy progressed electrophysiologically at a rate comparable with other studies in patients with type 1 [28] and type 2 diabetes [29]. Alterations in nerve conduction velocity and amplitude have been considered to reflect underlying structural pathology of the myelinated fibres [30].…”
Section: Discussionsupporting
confidence: 80%
“…Electrophysiological studies showed that muscle strength in diabetic patients correlated with fiber density and amplitude of the macromotor unit potential, suggesting incomplete reinnervation after axonal loss (32). Longitudinal studies suggest an average loss of compound muscle action potential amplitude at a rate of ϳ3%/year in patients with type 2 diabetes over a 10-year period (33). Further research should identify the role of the decrease in motor amplitudes on skeletal muscle strength and quality in subjects with diabetes.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…1,2 The most common forms are autonomic neuropathy and distal symmetrical polyneuropathy (DSPN) the latter being the most diagnosed in patients with diabetes mellitus (DM). 1,[3][4][5] Its prevalence fluctuates between 8 and 40% according to the clinical criteria or laboratory tests used for its diagnosis. [3][4][5][6] Most DM patients with DSPN are asymptomatic 3,7 and are symptomatic only in 15% of type 1 and 4-13% of type 2 (T2DM) patients.…”
Section: Introductionmentioning
confidence: 99%
“…1,[3][4][5] Its prevalence fluctuates between 8 and 40% according to the clinical criteria or laboratory tests used for its diagnosis. [3][4][5][6] Most DM patients with DSPN are asymptomatic 3,7 and are symptomatic only in 15% of type 1 and 4-13% of type 2 (T2DM) patients. 6,8,9 Early diagnosis and treatment are of great importance because (1) DSPN is the chief risk factor for trophic lesions and lower limb amputations in DM patients, 6,8,10,11 and around 85-96% of patients with DSPN are asymptomatic; (2) on occasion, neuropathies due to other aetiologies occur, requiring differential diagnosis; and (3) treatment at an earlier stage should improve prognosis.…”
Section: Introductionmentioning
confidence: 99%